Kajian Komposisi Sampah di Hotel Aston Kartika Grogol Jakarta - Pramiati Purwaningrum; Astari Minarti; Hernani Yulinawati; Yolanda Thasya Jocelin (Jurnal Serambi Engineering, 2023)
In order to reduce the volume of waste at the source, organic waste from restaurants namely food loss and food waste can be treated according to their characteristics. The purpose of the study is to determine the generation and composition of waste at Aston Kartika Hotel through the identification of the source of solid waste and analyze the composition of solid waste from each facility in Aston Kartika Hotel. The methodology of the research is carried out by undertaking the sampling of generation and waste composition in accordance with SNI 19-3964-1994. Aston Kartika Grogol Hotel with the source of solid waste from each facility. The total waste generation of Aston Kartika Grogol Hotel obtained from each facility amounting to 210.84 kg/day and the largest total waste generation of 81.84 kg/day coming from public areas. The largest fraction of waste composition was 35% of food waste and 17% of food loss which contributed organic waste by 52%. The most dominant type of inorganic waste was contributed by plastic waste consisting of types of HDPE, PVC, LDPE, PP, PES and PET. The composition of solid waste in Aston Hotel showed that 88% of hotel waste was suitable for recycling, while 12% of the total hotel waste was not suitable for recycling.